Heavy Equipment Rental Apps Using Ionic Framework - Tobias, Neec Chander (PT. Lentera Ilmu Publisher, 2024)
The study delves into the development of an Android-based heavy equipment rental application for PT. Gajah Unggul Internasional. The article underscores the significance of information systems in the heavy equipment rental business, introducing the specific context of PT. Gajah Unggul Internasional, a company providing various construction and industrial equipment. Recognizing the need for an efficient system to expedite processes such as borrowing, repaying, and restocking heavy equipment, the author proposes an Android application utilizing the Ionic Framework, a powerful open-source SDK. The methodology section outlines a meticulous five-stage research design, encompassing data collection, inception, elaboration, construction, and transition. The results and discussion section provides a detailed analysis of the application, including use case diagrams, activity diagrams, sequence diagrams, class diagrams, and the system interface. Black box testing validates the functionality and effectiveness of the proposed system, demonstrating successful outcomes in various aspects such as login, registration, equipment data viewing, and rental history tracking. In conclusion, the study showcases the successful integration of the Ionic Framework to enhance the efficiency and effectiveness of heavy equipment rental processes for PT. Gajah Unggul Internasional. The developed application offers a user-friendly interface catering to diverse stakeholders, emphasizing its practicality and functionality. Overall, the article contributes valuable insights into leveraging technology to streamline and optimize business operations in the heavy equipment rental industry.